ROLE OF OCEAN FISHING HARBOR BUNGUS IN THE ACTIVITIES OF FISHERIES IN WEST SUMATRA - Uci Gusdiana; Lamun Bathara; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted on 7 to 21 March. The purpose of this study was to evaluate the role of Ocean Fishing Harbor Bungus in the activities of fisheries in West Sumatra. The role refers to the terms of fleet size, fishing gear, production and the number of fishermen. The method was used is the survey method. The determination of the respondent in this are fishermen employees of PPS Bungus, in the harbor. The PPS Bungus which has a using Purposive Sampling. Descriptive analysis is done based on interviews with respondents and observations in cross check directly in the field. The results of this analysis, the number of fleets that fish landed as much as 4.32% (23 units) of 533 units. Fishing gear is used by 4.32% (23 units) of 533 fishing gear in PPS Bungus. The fish production average of 98.71 tons compared to the total production of 2321.88 tons per year. the majority of tuna, tuna and skipjack which were landed. The arresting and fishermen who sell fish in PPS Bungus were 3.17% (125 peoples) from of the total fishing activity in the harbor was 3939 people. PPS Bungus provide a small facility because the number of facility r is still in a small units and facilities are limited to function it, in addition the ocean harbor of fishing Bungus lack of security a causing the lack of users.Keywords: Role, Facilities, Activity Is Of Fisheries, Ocean Fishing Harbor Bungus